Redistribution of high energy alpha particles due to sawteeth with partial reconnection - Farengo, Ricardo (2013)
The redistribution of high energy alpha particles due to internal kink modes is studied in plasmas with ITER-like parameters. The exact particle trajectories in the total fields, equilibrium plus perturbation, are calculated. The equilibrium magnetic field is obtained by analytically solving the Grad–Shafranov equation and the perturbed electric and magnetic fields are reconstructed using ideal MHD and the experimental information about the displacement eigenfunction. The (1, 1), (2, 2) and (2, 1) modes are included and the effect of changing their amplitude and frequency is determined. The results show that if the conditions are similar to those reported in Igochine et al (2007 Nucl. Fusion 47 23), the peak density of counter-passing particles decreases between 25% and 40% (depending on the energy); the peak of the trapped particles density shifts outwards by approximately 10% of the minor radius and the total on axis density decreases by more than 25%. This redistribution occurs inside the q = 1 surface. The addition of a (2, 1) mode, which can produce the stochastization of the magnetic field, significantly increases particle redistribution and allows particles to spread beyond the q = 1 surface. Different groups of particles (co-passing, counter-passing, trapped) respond differently to the perturbations.